The Relationship of Islamic Human Development Index (I-HDI), ICT, and Governance to Poverty - Rozaq, Galilh Abdul; Darwanto, Darwanto (Jurnal Ilmiah Ekonomi Islam, 2024)
Poverty is the biggest problem facing the world today. Poverty is not just a statistical data, but in fact touches the lives of millions of people in the world. This study aims to examine the relationship between the Islamic Human Development Index (I-HDI), ICT, and Governance on poverty in D-8 countries in 2012-2022. D-8 countries are an association of developing Islamic countries in the world. In this study, the I-HDI value uses the Simple Weighted Index (SWI) by using a percentage of 20 on 5 dimensions of the index adjusted to the maqashid Sharia indicators. This research data uses 330 panel data and the research sample is selected through purposive sampling method in D-8 organization member countries. Based on this sampling method, 5 countries were selected as the object of this study, namely Indonesia, Malaysia, Egypt, Pakistan and Turkey. This research is processed through the Fixed Effect Model regression model. The regression model is used to test the relationship of 5 independent variables, namely I-HDI, Access to Information, Government Effectiveness (GE), Regulatory Quality (RQ), and Control of Corruption (CC) on the dependent variable, namely poverty. The results show that I-HDI, ICT, and Regulatory Quality (RQ) significantly reduce poverty. This study implies that D-8 member countries should use I-HDI as a measure of human development, maximize access to information technology, and improve regulatory quality to eradicate poverty.